2009
DOI: 10.1111/j.1365-2575.2007.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

IT project managers' construction of successful project management practice: a repertory grid investigation

Abstract: Although effective project management is critical to the success of information technology (IT) projects, little empirical research has investigated skill requirements for IT project managers (PMs). This study addressed this gap by asking 19 practicing IT PMs to describe the skills that successful IT PMs exhibit. A semi-structured interview method known as the repertory grid (RepGrid) technique was used to elicit these skills. Nine skill categories emerged: client management, communication, general management,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
126
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 47 publications
6
126
1
3
Order By: Relevance
“…Recognizing the key role played by PMs, the software project management literature specifies that PMs should have project management skills (Kirsch 2000), hard skills such as the requisite technical and domain expertise (Thite 1999), and soft skills such as client management, communication, general management, leadership, and team development skills, among others (Napier et al 2009, El Sabaa 2001. In addition to PM skills, the literature highlights the importance of using standard processes to optimize project delivery (Harter et al 2000, Gopal et al 2002, appropriate risk management frameworks (e.g., Wallace et al 2004), and requisite planning and management tools (Gopal and Gao 2009).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognizing the key role played by PMs, the software project management literature specifies that PMs should have project management skills (Kirsch 2000), hard skills such as the requisite technical and domain expertise (Thite 1999), and soft skills such as client management, communication, general management, leadership, and team development skills, among others (Napier et al 2009, El Sabaa 2001. In addition to PM skills, the literature highlights the importance of using standard processes to optimize project delivery (Harter et al 2000, Gopal et al 2002, appropriate risk management frameworks (e.g., Wallace et al 2004), and requisite planning and management tools (Gopal and Gao 2009).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…364-384, © 2014 INFORMS Our study makes significant contributions to the literature on project management, which often takes a "universalist" perspective and focuses on best practices to be applied across projects (e.g., Shenhar 2001, Harter et al 2000, Kirsch et al 2002, Gopal et al 2002, Wallace et al 2004, Project Management Institute 2008, Napier et al 2009). We extend this literature by (i) introducing and conceptualizing PI as an important capability for PMs that helps in resolving incidents that are situational and embedded in a particular project context; (ii) providing compelling empirical evidence that PMs' PI is efficacious in improving objective measures of project performance, unlike prior studies of PM capabilities that have been limited to conceptual arguments (Napier et al 2009) or have found little empirical support (Rai et al 2009);and (iii) identifying characteristics of the project context-to wit, complexity, and familiaritythat moderate the effect of PMs' PI on project outcomes (Venkatraman 1989, Shenhar 2001. We also contribute to the literature on offshore outsourcing, which has examined issues such as contracting inefficiencies, but has not often considered PMs' contribution to project performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are more important in ensuring that a technical task or duty is performed properly [13]. Technical skills are emphasized heavily in a classroom situation especially at universities or colleges and are given much attention in the field of research and also academia [2], [13].…”
Section: A Skills For Software Project Stakeholdersmentioning
confidence: 99%
“…People who are working within SDPs need to possess two sets of skills, namely soft skills and technical skills [13]. Soft skills are a cluster of sets of skills that influence the way in which people perceive, plan and execute tasks or duties within an SDP [2].…”
Section: A Skills For Software Project Stakeholdersmentioning
confidence: 99%